Analysis of the Fifth European Union Anti-Money Laundering Directive and its impact on financial institutions - Buyanova, Vlada (Riga Graduate School of Law, 2019)
Money laundering was and is a subject of great concern for many global financial institutions and national governments, as it is a crime with significant consequences. The European Union took several initiatives in order to strengthen its anti-money laundering framework. Thus, the 5th European Union Anti-Money Laundering Directive was adopted in June 2018. The research question of this paper is - what are the main requirements of the 5th European Union Anti-Money Laundering Directive and their impact on financial institutions? The author answers this question by employing doctrinal legal research and interdisciplinary methods. The obtained answer states that the Fifth Directive significantly strengthened the EU anti-money laundering defense, but also added high costs to financial institutions. However, further research is recommended in order to find possible practical and legal solutions to money laundering offenses and investigate the influence of developing legal instruments on the work of financial institutions.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Money laundering